The Gene Expression Biomarkers for Chronic Obstructive Pulmonary Disease and Interstitial Lung Disease - Yao, Yangwei; Gu, Yangyang; Yang, Meng; Cao, Dakui; Wu, Fengjie (Frontiers in Genetics, 2019)
COPD (chronic obstructive pulmonary disease) and ILD (interstitial lung disease) are two common respiratory disease. They share similar clinical traits but require different therapeutic treatments. Identify the biomarkers that are differentially expressed between them will not only help the diagnosis of COPD and ILD, but also provide candidate drug targets that may facilitate the development of new treatment for COPD and ILD. Due to the irreversible complex pathological changes of COPD, there is very limited therapeutic options for COPD patients. In this study, we analyzed the gene expression profiles of two datasets: one training dataset that includes 144 COPD patients and 194 ILD patients, one test dataset that includes 75 COPD patients and 61 ILD patients. Advanced feature selection methods, mRMR (minimal Redundancy Maximal Relevance) and Incremental Feature Selection (IFS), were applied to identify the 38-gene biomarker. An SVM (Support Vector Machine) classifier was built based the 38-gene biomarker. Its accuracy, sensitivity and specificity on training dataset evaluated by leave one out cross validation were 0.905, 0.896 and 0.912, respectively. And on independent test dataset, the accuracy, sensitivity and specificity on were as great as and were 0.904, 0.933 and 0.869, respectively. The biological function analysis of the 38 genes indicated that many of them can be potential treatment targets that may benefit COPD and ILD patients.